Optimizing Police Performance: The Role of Standard Operating Procedures (SOP) and Work Ethic in Enhancing Service Quality at the Integrated Police Service Center of Bekasi District - Alviyandi Alviyandi; Asep Jamaludin; Nandang Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
The implementation of Standard Operating Procedures (SOPs) is an essential guideline for managing the flow of tasks and responsibilities, while work ethic plays a crucial role in enhancing motivation and commitment to carrying out duties. This study aims to examine whether the Bekasi Metro Police SPKT (Integrated Police Service Center) section experienced changes in performance after the application of SOPs and work ethic. The study employs a quantitative, verification-based methodology. The research population consisted of 34 police officers from the SPKT section of the Bekasi Metro Police. Data analysis was conducted using SPSS version 27 software to test the hypotheses. The results revealed that the application of SOPs significantly influenced the performance of police officers, with a t-count value of 104.374, which was higher than the t-table value of 2.040. However, work ethic did not significantly affect police performance, with a t-count value of 1.895, which was lower than the t-table value of 2.040. Simultaneously, both the application of SOPs and work ethic had a significant impact on police performance, as indicated by an F-count value of 14.371, which was higher than the F-table value of 3.29. Together, the application of SOPs and work ethic explained 72.2% of the variance in police performance, while 27.8% was influenced by other factors.